2015
DOI: 10.1111/den.12581
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic features associated with development of metachronous gastric cancer in patients who underwent endoscopic resection followed by Helicobacter pylori eradication

Abstract: Absence of IM before ESD and emergence of map-like redness after HP eradication were useful endoscopic findings in the negative and positive prediction of metachronous gastric cancer developing after ESD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 27 publications
1
49
1
Order By: Relevance
“…In our study, about 55% of patients in which erosion was detected were H. pylori negative (Table 2), indicating that erosion is not an accurate indicator of the presence or absence of H. pylori infection. Patch redness has also been suggested as an indicator of H. pylori eradication [24]. In this study we observed patchy redness in only 4 patients, and although all 4 patients were H. pylori negative, we feel that this number of cases is insufficient to draw a reliable conclusion.…”
Section: Discussioncontrasting
confidence: 57%
“…In our study, about 55% of patients in which erosion was detected were H. pylori negative (Table 2), indicating that erosion is not an accurate indicator of the presence or absence of H. pylori infection. Patch redness has also been suggested as an indicator of H. pylori eradication [24]. In this study we observed patchy redness in only 4 patients, and although all 4 patients were H. pylori negative, we feel that this number of cases is insufficient to draw a reliable conclusion.…”
Section: Discussioncontrasting
confidence: 57%
“…LCI enables the detection of not only bluish-whitish patchy areas in NBI as LCS but also GIM as mottled patchy erythema and map-like redness, which typically appear after H. pylori eradication in patients with severe atrophy [25,26]. Actually, if WFE and mottled patchy area in the antrum were defined as GIM in WLI, the sensitivity of detection of GIM in WLI for our subjects was 29.3%.…”
Section: Discussionmentioning
confidence: 91%
“…Moribata et al . revealed that emergence of map‐like redness was identified as the only independent predictors for the development of metachronous EGC after successful H. pylori eradication in patients who underwent endoscopic submucosal dissection for EGC.…”
Section: Endoscopic Findings With Regard To Risk Of Gastric Cancermentioning
confidence: 99%
“…However, the total score of this grading system after H. pylori eradication therapy may not reflect the accurate risk of gastric cancer because of the disappearance of diffuse redness, nodularity, and enlarged folds. Furthermore, map‐like redness and the absence of RAC were identified as independent risks of gastric cancer after H. pylori eradication . Therefore, a new grading system, which includes the findings of mucosal atrophy, intestinal metaplasia, map‐like redness and RAC, will be required to determine a risk of gastric cancer in patients with past H. pylori infection.…”
Section: Evaluation Of Gastric Cancer Risk According To Kyoto Classifmentioning
confidence: 99%